Electrocatalysis of Perovskites: The Influence of Carbon on the Oxygen Evolution Activity. Issue 6 (16th March 2015) - Mohamed, Rhiyaad; Cheng, Xi; Fabbri, Emiliana; Levecque, Pieter; Kötz, Rüdiger; Conrad, Olaf; Schmidt, Thomas J.
Abstract : Single and double perovskite oxides have been reported to be amongst the most active electrocatalysts for the oxygen evolution reaction (OER) in alkaline electrolyte. Although a detailed study of the bulk electronic structure-activity relationship towards oxygen evolution on these oxides has been reported, the influence of carbon on the behavior of these oxides as OER catalysts is not yet clearly understood. In the present work we study the influence of functionalized acetylene black (ABf ) carbon in the electrode composition on the OER activity for perovskite oxides using the thin-film rotating disk electrode technique. It was found that the addition of ABf significantly enhances the OER activity of the single perovskite oxides, namely Ba0.5 Sr0.5 Co0.8 Fe0.2 O3-δ, (BSCF) and La0.6 Sr0.4 Co0.2 Fe0.8 O3-δ (LSCF). The activity of the double perovskite oxide, (Pr0.5 Ba0.5 )CoO3-δ (PBCO), was relatively unaffected by the addition of ABf in the electrode. Ex situ impedance spectroscopy measurements at room temperature showed that BSCF powder displayed a lower resistivity compared to PBCO with LSCF displaying the highest resistivity of the three materials. These results therefore suggest that the ABf present can more than simply improve the conductive pathway in the perovskite/carbon composite electrodes but can also significantly enhance the electrocatalytic activity of selected perovskites towards the OER.